A Portrait About Writing Explanatory Skill of Fifth-Grade Elementary School - Palupi, Bening Sri; Subiyantoro, Slamet; Rukayah, Rukayah (International Journal for Educational and Vocational Studies, 2019)
Indonesia has implemented the 2013 curriculum as a text-based learning framework. The text is used as a defender of science. The logical consequence, language skills are an absolute requirement for students so that they can achieve learning goals. On the other hand, writing is the highest skill in the language. Therefore, the study was aimed to describe the explanatory writing skills of fifth-grade elementary students. This research is a descriptive qualitative study using a sample of fifth-grade students in public elementary schools in the city of Surakarta, Central Java, Indonesia. Data collection techniques using documents and interviews. Source triangulation is used as data validity. The results showed that the greatest difficulty students had in writing explanations was writing cohesive and coherent sentences and paragraphs. They are only able to write their ideas without regard to syntactic rules. These writing skills involve students' metacognitive skills which also reflect other language skills such as listening and reading. This research output will be useful for academics and practitioners in determining the right learning approach to improve the success of text-based learning or the 2013 curriculum.